To propose a model of family education that achieves social development in urban areas. - mansouri, abdelaziz (Journal of Social Sciences and Humanities, 2025)
The urban community is characterized by a number of specificities that distinguish it from other communities, especially in relation to the nature of its ecological structure and cultural structure, which contribute to the characterization of individuals within this society with certain educational and cultural characteristics. Social development within the urban community stands out as a central societal process linked to a variety of societal indicators that are in one way or another related to a particular societal system, including the family system, where the effects of family education in its various ways determine the course and nature of social development in different forms. In this paper, we will attempt to present a proposed scenario for a model of a qualitative and dynamic family education method that contributes in one way or another to the social development of individuals within the urban community, through strategies that go beyond the obstacles of social development first and propose alternatives and methods of family education.